Epic features of the creation of the world in the heroic epic of the Mari people "Yugorno. The Song of the Prophetic Path" - Galina E. Shkalina (Этническая культура)
The article is devoted to the study of cosmogonic narratives of the Mari people. The goal: to identify the epic features of the creation of the world in the heroic Mari epic "Yugorno. Song of the Prophetic Path" against the background of epic works known in the global context. The materials are both the poetic creation of A. Ya. Spiridonov "Yugorno. Song of the Prophetic Path" and the author's field materials on the multi-level system of concepts reflecting the natural, cultural, social and virtual realities of the past, present and future in the worldview of the Mari people. The work is based on the hermeneutic-phenomenological approach to the study of epic texts using problematic and historical-comparativistic methods. Conclusion: widely popular ideas of people about the world order are reflected in the folk heroic epic as an immanent contradiction between two opposite principles present in the very essence of being (top-bottom, right-left, white-black, etc.). In the Mari poetic creation "Yugorno" the epic features of the creation of the world were expressed not in the harsh antagonism of the hero and the antihero, but in the peaceful competition between the gods-creators of different parts of the Universe, understood by people as good and evil due to the objective duality of the world.